2013
DOI: 10.1517/14728222.2012.741122
|View full text |Cite
|
Sign up to set email alerts
|

The potential of carboxypeptidase M as a therapeutic target in cancer

Abstract: CPM is a part of the molecular signature of many cancers. There is good evidence that it is useful for the discrimination and stratification of cancer types, possibly in combination with other markers such as EGFR and MDM2. Whether it is also a drug target remains to be determined. Lung, kidney, brain, and the reproductive system contain relatively high levels of CPM, but its functions in those tissues are largely unknown. CPM is expressed on tumor-associated macrophages. To facilitate the investigation of CPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 87 publications
0
18
0
Order By: Relevance
“…CPs are zinc-dependent enzymes that have been reported to be correlated with a range of physiological and biological processes, such as oncogenesis. For example, carboxypeptidase E (CPE) is suggested to be dysregulated and participate in the metastases of serval human malignancies, 13,24 highlighting the vital role of certain CPs in the regulation of malignant biological properties. To date, some CPs have been recognized as potential therapeutic and diagnostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPs are zinc-dependent enzymes that have been reported to be correlated with a range of physiological and biological processes, such as oncogenesis. For example, carboxypeptidase E (CPE) is suggested to be dysregulated and participate in the metastases of serval human malignancies, 13,24 highlighting the vital role of certain CPs in the regulation of malignant biological properties. To date, some CPs have been recognized as potential therapeutic and diagnostic biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Although not all CPs exhibit active peptidase activity, members of the M14 family have various physiological functions on account of their substrate specificity, tissue distribution, and cellular and subcellular localization. 12,13 Carboxypeptidase X (CPX), M14 family member 2 (CPXM2) is a member of the M14 family and has been shown to be associated with several developmental disorders by affecting the cell-cell interactions. [14][15][16][17] To date, the impact of CPXM2 on HCC tumorigenesis has not been further explored.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has shown elevated expression of CPA3 in asthma (43) and anaphylactic shock (44); however, few studies have investigated the role of CPA3 in cancers. CPM is also an arginine/lysine CP and exerts important roles in angiogenesis, proliferation, and apoptosis through modulating chemokines or kinins in cancer cells (45). Notably, recent study reports that CPM/Src-FAK pathway is involved in the cell migration and invasion in colon cancer (46).…”
Section: Discussionmentioning
confidence: 99%
“…CPM was less reported, and only one literature revealed that it was the target of miR-146a which promoted cell migration and invasion in CRC via CPM/src-FAK pathway ( 34 ). It was suggested that CPM has the potential to be a therapeutic target in cancer ( 35 ), but its function still need further discovery. SHMT2 participated in the cellular one-carbon metabolism, and has been implicated as a critical component for tumor survival.…”
Section: Discussionmentioning
confidence: 99%